Pollen morphology of Ternstroemia Mutis ex L.f. (Pentaphylacaceae): describing morphological variations in a stenopalynous taxon - Gasparino, Eduardo Custódio [UNESP]; Cerdan, Isaura de Paula; Dutra, Fernanda Vitorete [UNESP]; Vieira, Jaqueline Alves [UNESP]; Sampaio, Daniela [UNESP] (Palynology, 2025)
Currently classified within the Ericales, Pentaphylacaceae comprises 511 species and 14 genera with tropical and subtropical distributions. Ternstroemia, the genus with the most species of the family, exhibits the greatest diversity and the broadest geographic range within the family, with Brazil hosting the highest number of species. The species within this genus are challenging to delineate due to their morphological similarities, particularly in floral organs, with no detailed descriptions of their pollen morphology. This study aimed to morphologically analyze the pollen of eight Ternstroemia species and Freziera atlantica (a related Brazilian species), providing both qualitative and quantitative data on pollen grains that could help in species delimitation. Pollen grains were acetolyzed and measured, qualitative data was described, and quantitative data was analyzed using descriptive statistics. Stamen data were added to the pollen data for multivariate analyses. An artificial pollen key and illustrations in light microscopy (LM) and scanning electron microscopy (SEM) are presented. Ternstroemia pollen grains are monads, isopolar, small to medium, prolate spheroidal or subprolate, 3-colporate, and microreticulate. The ornamentation, presence of a costa, and a lalongate endoaperture may serve as diagnostic features for the genus, since in F. atlantica we observed psilateperforate pollen, without a costa and with a circular endoaperture. Despite consistent pollen morphology, features such as amb, ectoaperture length, and the shape and position of the apertures help distinguish Ternstroemia species.
Pollen morphology of Ternstroemia Mutis ex L.f. (Pentaphylacaceae): describing morphological variations in a stenopalynous taxon
Keywords: Ericales; Palynology; Pollen grains; Taxonomy